Church and society, a study of the social work and thought of James Begg, D.D. (1808-1883), A.H Charteris, D.D., LL.D (1835 - 1908), and David Watson, D.D. (1859 - 1943) - Bishop, Donald H. (The University of Edinburgh, 1953)
This dissertation is a study of the social work and thought of three eminent Scottish ministers whose major contributions to the Church and society came in the years from 1835 to 1935# Br. James Begg, Br. A. H. Charteris, and Br. navid Watson lived at a time when the Industrial Revolution was bringing about many changes and up¬ heavals in Scottish social, religious, political and economic life. Social institutions, customs, habits, and patterns of thought and behaviour were constantly undergoing transition and alteration. The new conditions created by the Industrial Revolution had an effect upon the Church as well} and her reaction and adjustment to those changes and the contributions of the three men to the Church in that process has been the central theme of this work